Comparative efficacy of tislelizumab plus lenvatinib and tislelizumab alone against advanced hepatocellular carcinoma after lenvatinib failure: a real-world study - Jiajin Yang; Qiuping Xu; Sihao Luo; Jianbing Wu (BMC Cancer)
Abstract This study evaluated the effectiveness and safety of tislelizumab plus lenvatinib (TL group) and tislelizumab monotherapy (T group) in patients with stage C hepatocellular carcinoma (HCC) according to the Barcelona Clinic Liver Cancer (BCLC) staging system after lenvatinib failure, and it analyzed the factors influencing the effectiveness of TL as a second-line treatment. This retrospective analysis involved 51 patients treated at a single center between January 2019 and July 2023. Survival outcomes and tumor responses were compared between the TL and T monotherapy groups. Prognostic factors for overall survival (OS) and progression-free survival (PFS) were identified using Cox proportional hazard regression models. Among patients with BCLC stage C advanced HCC who experienced lenvatinib treatment failure, median PFS was significantly longer in the TL group than in the T group (6.8 months vs. 4.5 months, p = 0.003), and OS was notably extended in the TL group (14.0 months vs. 10.4 months, p = 0.012). Although the disease control rate (64% vs. 53.8%, p = 0.461) and objective response rate (20% vs. 7.7%, p = 0.202) were numerically higher in the TL group, these differences did not reach significance. Child–Pugh B liver function and tislelizumab monotherapy were independent prognostic factors for poor OS, whereas only tislelizumab monotherapy was an independent prognostic factor for poor PFS, Child-Pugh B was not a prognostic factor for PFS. Subgroup analysis demonstrated the OS benefit of tislelizumab plus lenvatinib in patients with Child–Pugh A liver function (14.0 months vs. 12.0 months, p = 0.013) but not in those with Child–Pugh B liver function (7.7 months vs. 6.1 months, p = 0.225). In the TL group, the most frequent treatment-related adverse events (AEs) were hand–foot skin reaction (32%), hypertension (28%), diarrhea (32%), and hypothyroidism (20%). Grade 3 or higher AEs occurred in 24% of patients in the TL group, and hand–foot skin reaction and diarrhea were the most frequent grade 3 or higher AEs. The incidence of AEs was comparable between the two groups. As a second-line treatment, the combination of tislelizumab and lenvatinib was well tolerated and associated with improved OS and PFS versus tislelizumab alone for patients with advanced HCC, particularly in those with Child–Pugh A liver function.